Prolonged Field Care Research Approach and Its Relevance to Civilian Medicine. - Cohen, Adam B; Davis, Michael; Herman, Sarah E M (Military Medicine)
In early March 2020, Johns Hopkins University Applied Physics Lab hosted an Association of Military Surgeons of the United States regional conference to address medical demands of the future battlefield for which prolonged field care is expected. Arising from this conference, we propose here an approach to prolonged field care research-and also summarize the major concepts discussed at the conference. We draw parallels to prolonged field care investments and advancements that apply beyond the combat environment. The exceedingly daunting medical challenges of the future battlefield, on land and at sea, must be addressed to maintain an effective force able to compete with modern highly capable adversaries. Since the human element, and its health, will allow future mission success, we propose here an approach to making soldier health-related research most impactful.